Validation of the Korean Version of the Multidimensional Assessment of Interoceptive Awareness for Adolescents (K-MAIA-A) Using the Rasch Model - Eun-young Kim (Jounral of Educational Therapist, 2026)
This study examined the psychometric properties of the Korean version of the Multidimensional Assessment of Interoceptive Awareness for Adolescents (K-MAIA-A), which multidimensionally assesses adolescents’ awareness, attention, regulation, and attitudes toward internal bodily sensations. Based on the MAIA-y, five items from the MAIA-2 were added and modified, resulting in 37 preliminary items. Data were collected from middle and high school students through a preliminary survey (N = 336) and a main survey (N = 459). Exploratory factor analysis, guided by the theoretical eight-factor structure, showed that the Not-Distracting and Not-Worrying factors failed to meet the criteria and were excluded. A final six-factor, 20-item structure was identified: Noticing, Attention Regulation, Emotional Awareness, Self-Regulation, Body Listening, and Trusting. Rasch analysis examined item difficulty, item fit, and the appropriateness of response categories, while confirmatory factor analysis supported the stability of the factor structure. Correlations with related scales further supported the validity of the K-MAIA-A. The scale provides an integrated assessment for understanding the development of interoceptive awareness in adolescents and offers practical implications for counseling interventions and monitoring therapeutic change.